2015
DOI: 10.4172/2167-7670.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Modelling in Squeeze Casting Process-Present State and Future Perspectives

Abstract: The growing demand in today's competitive manufacturing environment has encouraged the researchers to develop and apply modelling tools. The development and application of modelling tools help the casting industries to considerably increase productivity and casting quality. Till date there is no universal standard available to model and optimize any of the manufacturing processes. However the present work discusses the advantages and limitations of some conventional and non-conventional modelling tools applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Macrosegregation has a significant effect on the mechanical properties of the final cast part as well as on the productivity of this process. In addition, machining operations are required to remove the defects which in turns it makes necessary a larger casting to allow for the machining, [15][16][17] and additional machining operations call for longer durations of production.…”
Section: Introductionmentioning
confidence: 99%
“…Macrosegregation has a significant effect on the mechanical properties of the final cast part as well as on the productivity of this process. In addition, machining operations are required to remove the defects which in turns it makes necessary a larger casting to allow for the machining, [15][16][17] and additional machining operations call for longer durations of production.…”
Section: Introductionmentioning
confidence: 99%
“…Ramón Ángel et al aimed to optimize the production of grey cast pump impellent castings using Response Surface Methodology (RSM) approach in a foundry producing grey cast iron components [7]. Manjunath Patel et al discuss about the advantages and limitations of some conventional and non-conventional modelling tools applied for various casting processes and the necessary steps for prediction and optimization are high lightened by identifying the trends in the literature [8]. However, it was observed that processing methods [9][10][11], casting geometry and size [12], physical and chemical conditions [13], mold and casting material properties [14], process variables [15][16][17] and so on directly affect the Heat Transfer Coefficient (HTC).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%